Narratives of the Selves and the (in)Tangibility of Vibrant Matter - Paramehta, Teraya (Jurnal Filsafat "WISDOM", 2025)
Focusing specifically on how self-narratives transform narratives of other things, the paper focuses on the category of (in)tangibility in vibrant matter. How and in what ways does the (in)tangible quality of things matter in matters and how does it transform the material relationship of narratives? Engaging with theories of new materialism, such as Jane Bennett’s “thing power” and “distributive agency,” and Mel Chen’s discussion on animacy in language, the paper is also in conversation with the genealogy of affective hapticity and the Western tradition of self-narrative. Responding to Jane Bennett’s question on humans and things, the paper suggests that (in)tangibility of matter may offer us a way to better navigate the language gap between things and humans. The paper argues that pausing at moments of (in)tangible processes will make visible how narratives have their own narratives despite the seemingly anthropocentric nature of our reading of narratives. Placing human subjectivities not as the only producers of narratives, the paper demonstrates that things, too, share certain narratives that exist adjacent to the Anthropocene.